2019
DOI: 10.1161/strokeaha.118.024092
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Factors Associated With Concordance Between International Classification of Diseases, Ninth and Tenth Revision, Clinical Modification Codes and Stroke Clinical Diagnoses

Abstract: Background and Purpose— International Classification of Diseases, Ninth and Tenth Revision, Clinical Modification ( ICD-9-CM and ICD-10-CM ) codes are often used for disease surveillance. We examined changes in concordance between ICD-CM codes and clinical diagnoses before and after the transition to ICD-10-CM in the United States (October 1, 2015), and determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“… 9 10 We identified patients whose date of hospital discharge was from April f1 to July 31 2020 and included those with ICD-10 codes for EVT and ischemic stroke ( online supplemental table 1 ). 11 12 The concordance between the clinical diagnosis of ischemic stroke and the used ICD-10 codes has previously been shown to be >95% 11 and the codes for mechanical thrombectomy are specific to a procedure, making the use of the code without performing the procedure unlikely. Patients<18 years of age and those who were in a hospice at the time of admission were excluded.…”
Section: Methodsmentioning
confidence: 99%
“… 9 10 We identified patients whose date of hospital discharge was from April f1 to July 31 2020 and included those with ICD-10 codes for EVT and ischemic stroke ( online supplemental table 1 ). 11 12 The concordance between the clinical diagnosis of ischemic stroke and the used ICD-10 codes has previously been shown to be >95% 11 and the codes for mechanical thrombectomy are specific to a procedure, making the use of the code without performing the procedure unlikely. Patients<18 years of age and those who were in a hospice at the time of admission were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Some patients with principal ICD-10-CM codes for stroke or TIA may not have been included in the registry. However, a study suggested that the concordance between ICD-10-CM codes and stroke clinical diagnosis was generally high in PCNASP, so misclassification would apply to a small number of patients ( 25 ). Finally, our study compared point prevalence data (pre-COVID-19 period in 2019 vs the early phase of the COVID-19 pandemic period in 2020); it did not examine the potential effects of long-term trends in stroke hospitalizations and quality of care because of the changes in the participating hospitals in PCNASP over time.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective cohort study included data from the Vizient Clinical Data Base (CDB), a health care analytics platform used by participating US hospitals for measuring clinical performance, costs, and outcomes. 18 We included patients who received a diagnosis of IS (based on International Statistical Classification of Diseases, Tenth Revision, Clinical Modification [ ICD-10-CM ] codes I63.x and H34.1 19 ) who were discharged from 478 hospitals that reported complete patient-level data from January 1, 2019, to December 31, 2020. Patients were eligible for inclusion if they were admitted to the hospital on a nonelective basis and were not receiving hospice care at the time of admission.…”
Section: Methodsmentioning
confidence: 99%